Elastic critical moment of continuous composite beams with a sinusoidal-web steel profile for lateral-torsional buckling. (15th April 2016) - de Oliveira, Janaina Pena Soares; Calenzani, Adenilcia Fernanda Grobério; Fakury, Ricardo Hallal; Ferreira, Walnório Graça
Highlights: LTB elastic critical moment of sinusoidal-web continuous composite beams is obtained. FEA model with ANSYS software to determine the elastic critical moment is developed. FEA model is evaluated against numerical data from the literature. Buckling analysis in forty-five FEA models with varying key parameters is performed. A procedure for predicting LTB elastic critical moment is proposed. Abstract: Lateral-torsional buckling (LTB) is an ultimate limit state that can occur in the hogging moment regions of continuous composite steel and concrete beams. This limit state is characterised by the buckling of the steel profile compressed flange (bottom flange) about the minor axis, together with a distortion of the steel profile web. The European Standard EN 1994-1-1:2004 provides an approximate procedure for LTB design that is applicable to continuous composite beams, but only those with a plane web steel profile. The most important step of this procedure is the determination of the elastic critical moment. In this paper, a finite element analysis (FEA) model was developed using the software ANSYS to determine the elastic critical moments of continuous composite steel and concrete beams with corrugated sinusoidal-web steel profiles, which were evaluated against numerical data from the literature. Ultimately, a study involving 45 models was conducted based on FEA modelling, and a procedure for predicting the elastic critical moment of composite beams with sinusoidal-web steel profiles was proposed.